Modeling the dynamics of heat and mass transfer processes in a tubular heat exchanger under pulsed influences - Sakipova, S.E.; Shaimerdenova, K.M.; Nussupbekov, B.R.; Ospanova, D.A.; Kutum, B.B. (Eurasian Physical Technical Journal, 2023)
The paper discusses the results of experimental studies of the influence of the degree of inhomogeneity of a liquid flow on the dynamics of heat and mass transfer processes under pulsed impacts. High-voltage electric discharges in a liquid medium were used as impulse actions, through which an electro-hydraulic effect is realized, accompanied by the appearance of shock waves. The dynamics of the occurring nonlinear, rapidly changing heat and mass transfer processes at high hydraulic pressures cannot be described using differential equations. The simulation was carried out on the basis of the method of group consideration of arguments, the advantage of which is the construction of polynomial dependencies using a small amount of experimental data. The results of constructing polynomial dependences made it possible to reveal the synergistic effect of the influence of flow parameters on the dynamics of the impulse pressure amplitude and the intensity of heat transfer.
Keywords: heat and mass transfer; tubular heat exchanger; diffuser; method of group consideration of arguments; impulse action; electrohydraulic effect; heat transfer rate